Candidatos à reeleição versus concorrentes: a competição eleitoral nas eleições legislativas no Estado de Minas Gerais em 2010 - Felipe Lima Eduardo (2012)
This research explores the competitiveness of the Brazilian legislative elections based on the classification of candidate profiles used in American literature. This classification consists of separating the candidates into three distinct profiles: the incumbents, the high-quality challengers, and the challengers. The dissertation sought to fit this categorization for the Brazilian electoral reality. The electoral performance of state and congressional candidates, running to represent the state of Minas Gerais, during the legislative elections of 2010 was compared, using the average results of each profile. Analyses were undertaken to view the performance of the candidates' profiles in different electoral contexts, in major and minor cities with larger and smaller Human Development Index (HDI). The use of bivariate and multivariate quantitative analysis techniques made it possible to measure the main differences between the electoral strength of each profile. In addition to proving the expected electoral superiority of the incumbents, and of the candidates with higher campaign expenditures, the work presented other dimensions that differentiate the electoral performance of each of the profiles analyzed. So it was possible to verify and quantify, in Minas Gerais, the existing imbalance in the state and federal legislative elections.